Progress towards a rapid method for conceptual aerodynamic design for transonic cruise - Prince, Simon A.; Di Pasquale, Davide; Garry, Kevin P. (AIAA, 2020)
Results are presented from a study aimed at demonstrating the accuracy and efficiency of a lower order aerodynamic prediction method for transonic cruise flows around aircraft configurations, including conventional swept wing-body and also blended wing-body designs. The Viscous Full Potential (VFP) method, coupling the solution of the full potential equations with the integral boundary layer equations can yield data of almost equivalent accuracy as Navier-Stokes based CFD methods but at 0.5% - 2% of the physical time. In addition it is shown, using both the VFP approach and Delayed Detached Eddy Simulation (DDES) that the flow physics of the stall mechanism associated with blended wing-body configurations is far more complex than that experienced on more conventional swept-tapered wings. The mechanism appears to involve an initial tip stall but also involves highly 3D vortical flows inboard on the upper surface of the wing which significantly distorts the transonic shock wave.